2010
DOI: 10.1002/dc.21270
|View full text |Cite
|
Sign up to set email alerts
|

Functional biomarkers in cervical precancer: An overview

Abstract: Cervical cancer develops over a long time through precursor lesions that can be detected by cytological screening. Majority of these lesions regress spontaneously. Therefore, the challenge of cervical cancer screening is to detect the lesions that have a high risk of progression. Several promising biomarkers have been described that may improve screening of cervical cancer, but to date, new biomarkers have not been thoroughly validated in high-quality studies. The knowledge about human papillomavirus as a caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 72 publications
1
15
1
2
Order By: Relevance
“…Cubilla et al (2011) demonstrated that HR-HPVs were correlated with p16INK4a positivity in ~80% of penile carcinoma cases, and suggested that p16INK4a negativity could indicate the HPV DNA absence or monoviral LR-HPV infection. Gupta et al (2010) showed higher p16INK4a expression in cervical HR-HPV lesions and a weak staining pattern in LR-HPV lesions, consistent with our data (Table 6). In this systematic review, meta-analysis and trails pointed out the difficulty of evaluating the use of p16INK4a immunohistochemistry for cytological and histological samples due to the lack of a standardized methodology.…”
Section: Discussionsupporting
confidence: 92%
“…Cubilla et al (2011) demonstrated that HR-HPVs were correlated with p16INK4a positivity in ~80% of penile carcinoma cases, and suggested that p16INK4a negativity could indicate the HPV DNA absence or monoviral LR-HPV infection. Gupta et al (2010) showed higher p16INK4a expression in cervical HR-HPV lesions and a weak staining pattern in LR-HPV lesions, consistent with our data (Table 6). In this systematic review, meta-analysis and trails pointed out the difficulty of evaluating the use of p16INK4a immunohistochemistry for cytological and histological samples due to the lack of a standardized methodology.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have suggested that testing the performance of p16 INK4a in combination with other biomarkers could improve its performance (Galgano et al 2010, Gupta et al 2010), but we were unable to assess combinations in this study. Another limitation is that the ROC/AUC values were obtained with a convenience sample, which limits the reproducibility of our findings.…”
Section: Discussionmentioning
confidence: 87%
“…18,19 In our study, the analysis of these biomarkers in biopsy material by immunohistochemistry showed that all were positive in a high proportion of the HSIL lesions, which is consistent with current evidence. 8,16,[20][21][22][23] Nevertheless, immunohistochemistry is not adequate for screening purposes. Finally, immunohistochemistry only analyzes a small area of the lesion, which may not be representative of the whole process that could explain the absence of correlation between the mRNA expression in the liquid-based cytology and the immunohistochemistry staining in the simultaneous biopsy for most of the biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Recently, Bourmenskaya et al 30 have shown that a gradual increase in the expression of proliferation markers and a decrease in the expression of pro-apoptotic human genes, as determined by RT-PCR, were associated with increased risks of carcinogenesis. These authors proposed a quantitative model combining the expression of CDKN2A/p16 and BIRC5, which are associated with adverse prognosis, 31,32 and MKI67, which distinguish SIL from normal or benign reactive cervical lesions, 22 for cervical cancer risk assessment. Our results also indicate that a combination of biomarkers could be an adequate strategy for HSIL detection.…”
Section: Discussionmentioning
confidence: 99%